Peran Peradi terhadap Advokat yang Melakukan Pelanggaran Kode Etik Profesi Advokat - A, Irham Wandira; Suheri, Muhammad; Zahara, Fatimah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The legal profession is closely related to the bar association as a place for lawyers. The legal profession is a respected profession (officium nobile) because it devotes itself to the interests of the community, not just for personal gain. One of the roles of a lawyer is as a supervisor and guardian of justice. However, in its implementation and enforcement, it is often seen that the lawyer's code of ethics is not given much attention by most lawyers. Violations of the code of ethics are often committed by lawyers in carrying out their profession, and they are not hesitant to do so openly. If there is a violation of the code of ethics, the Bar Association has the right to impose sanctions in accordance with the articles stipulated in the Indonesian Code of Ethics for Lawyers, as stated in Article 7 paragraph (1) of the Indonesian Code of Ethics for Lawyers Law. This study is a normative legal research group, namely legal research that uses the type of doctrinal research or also called normative juridical research (legal study research).